GeoChip 4: a functional gene‐array‐based high‐throughput environmental technology for microbial community analysis. (14th March 2014) - Tu, Qichao; Yu, Hao; He, Zhili; Deng, Ye; Wu, Liyou; Van Nostrand, Joy D.; Zhou, Aifen; Voordeckers, James; Lee, Yong‐Jin; Qin, Yujia; Hemme, Christopher L.; Shi, Zhou; et al.
Abstract Micro‐organisms play critical roles in many important biogeochemical processes in the Earth's biosphere. However, understanding and characterizing the functional capacity of microbial communities are still difficult due to the extremely diverse and often uncultivable nature of most micro‐organisms. In this study, we developed a new functional gene array, GeoChip 4, for analysing the functional diversity, composition, structure, metabolic potential/activity and dynamics of microbial communities. GeoChip 4 contained approximately 82 000 probes covering 141 995 coding sequences from 410 functional gene families related to microbial carbon (C), nitrogen (N), sulphur (S), and phosphorus (P) cycling, energy metabolism, antibiotic resistance, metal resistance/reduction, organic remediation, stress responses, bacteriophage and virulence. A total of 173 archaeal, 4138 bacterial, 404 eukaryotic and 252 viral strains were targeted, providing the ability to analyse targeted functional gene families of micro‐organisms included in all four domains. Experimental assessment using different amounts of DNA suggested that as little as 500 ng environmental DNA was required for good hybridization, and the signal intensities detected were well correlated with the DNA amount used. GeoChip 4 was then applied to study the effect of long‐term warming on soil microbial communities at a Central Oklahoma site, with results indicating that microbial communities respond to long‐term warming by enriching carbon degradation, nutrient cycling (nitrogen and phosphorous) and stress response gene families. To the best of our knowledge, GeoChip 4 is the most comprehensive functional gene array for microbial community analysis.